Пране Дундулене: увічнення пам’яті - Васіляускене А. (Народна творчість та етнологія, 2011)
The article enlightens a figure of the first doctor of ethnography (now – ethnology), habil. dr., Prof. Pranė Stukėnaitė-Dundulienė (12.02.1910–27.02.1991), her life and activities. The heed is paid to her scientific work which has a huge importance for the Lithuanian science, the realities of her good name’s perpetuation are discussed, as well as showed are the visions of bestowal of honours.